Nothing about us without us! How users configure clinical treatment in Italian residential communities: ethnography of therapeutic engagement - Iudici, Antonio; Berardelli, Tobia; Fenini, Davide; Neri, Jessica; Subissi, Emiliano (Frontiers in Public Health, 2024)
The effectiveness of the interventions in the Therapeutic communities (TC) depends not only on the quality of the specialized knowledge and methodologies adopted, but also on the meanings consumers give to them. Building the therapeutic alliance is a key element in reducing high drop-out rates and predicting more favorable outcomes. This research investigated the discourses practiced by 45 people with substance use disorders who had been accessing a therapeutic community for less than 15 days, with the aim of delving into the meanings given to treatment and pathway goals in the service, to analyze what theories are used to explain consumption and therapeutic change. The study made use of Discourse analysis (DA) and Positional theory with a protocol of written open-ended questions. The results show how participants configure the community pathway adopting a passive role, underestimating the need to co-participate in treatment design and bringing in poorly formalized goals. The collected texts provide a better understanding of the perspective of community users, emphasizing the need to share spaces of co-design from the very beginning in order to promote empowering, reasoning about the implications of the various discourses produced by consumers to explain their autobiography and to envision paths of change.